Strategies for adapting the dense Italian cities to the climate change: The case study of the San Salvario historical neighborhood - Ingaramo, Roberta; Negrello, Maicol (TeMA - Journal of Land Use, Mobility and Environment, 2024)
The urban fabric of European cities is subject to significant pressures from human activity and climate change. The devastating effects of climate change on urban environments threaten the quality of life of citizens and ecosystems. In particular, historic and dense cities face challenges in adapting their established urban fabric devoid of green areas. The lack of green spaces for social gatherings becomes a critical issue in addressing the climate and environmental crisis. This essay identifies the 19th-century neighbourhood of San Salvario in Turin, Italy, as a case study to develop a morphological analysis aimed at proposing nature-based strategies to improve the adaptation potential and resilience of this urban fabric. The analysis also compares European best practices, such as the cities of Barcelona and Copenhagen, which serve as examples of adaptive planning. The design elements identified in these two case studies provide inspiration for hypothesising replicable architectural solutions in dense urban contexts such as the study area under consideration. Finally, the paper addresses the limitations arising from the lack of holistic strategic planning, which in the case of Turin is based on fragmented interventions disconnected from the existing ecological network rather than on a long-term plan. The paper also reflects on the need to include additional assessments of ecosystem services, taking into account their economic valuation.